PERAN PUBLIC INFORMATION OFFICER DAN DATA ANALYST DALAM PROGRAM GOVERNMENT PUBLIC RELATIONS LAPOR SEMAR SOLUSI AWP - Christopher Fabian Polo; Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Lapor Semar Solusi AWP is a digital public service managed by the Semarang City Communication, Informatics, Statistics, and Persandian Office (DISKOMINFO). This platform handles public reports regarding infrastructure and government services, while also serving as a hub for citizens to voice their aspirations for the city's development. Before the current Mayor, Agustina Wilujeng Pramestuti, took office, the service operated under various names, including Sapa Mbak Ita and Lapor Hendi. Since rebranding to Lapor Semar Solusi AWP in April 2025, the platform has seen lower user engagement and public awareness levels compared to its previous iterations. To address these challenges, a government public relations approach was implemented using a combination of public service and education campaigns, media relations, paid advertisements, and owned media. The primary objectives of this strategy are to boost public knowledge and strengthen community trust, which are essential for increasing the service's user base. The implementation revealed that paid advertisements were the most effective method for expanding reach and increasing general awareness among Semarang residents. On the other hand, public service and education campaigns proved to be the most successful in building public trust and driving the acquisition of new service users.